Analisis Pembiasaan Harian Terhadap Pembentukan Karakter Peserta Didik - Annisa'ul Mufidah; Yuliati Sari; Bayu Widiyanto (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2023)
Today the lives of Indonesian citizens are experiencing moral degradation, especially among students, this requires the holding of character education. Schools are required to be able to carry out their roles and responsibilities to instill and develop good character values ​​and help students shape and build their character with good values ​​Teachers need to design learning, identify children's level of knowledge, motivate children and make activities learning fun. This research is a type of qualitative research. The approach used is descriptive qualitative to analyze the habituation carried out at SDN Tegal Gede 01. The purpose of this study is to analyze the daily habituation carried out at SDN Tegal Gede 01 towards the formation of students' character. Based on the results of observations and interviews, researchers can conclude that the habits that are carried out at SDN Tegal Gede 01 in developing the character of students are through daily routine activities, spontaneous activities and exemplary activities. Habituation activities carried out in schools can foster a positive attitude in students. Character education not only has a positive impact on students, character education through this habituation also improves the teacher's character or personality in developing core ethical and aesthetic values ​​such as caring, honesty, fairness, responsibility, and respect for self and others